2023
DOI: 10.3892/mmr.2023.12975
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol extracts from Anemone flaccida Fr. Schmidt treat rheumatoid arthritis via inhibition of synovial hyperplasia and angiogenesis

Abstract: Anemone flaccida Fr. Schmidt, a Traditional chinese Medicine, has been used in the treatment of rheumatoid arthritis (RA) for numerous years. However, the specific mechanisms remain to be elucidated. Thus, the present study aimed to investigate the main chemical constituents and potential mechanisms of Anemone flaccida Fr. Schmidt. The ethanol extract obtained from Anemone flaccida Fr. Schmidt (eaF) was analyzed using mass spectrometry to determine the main components and the therapeutic effects of eaF on RA w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
(40 reference statements)
0
1
0
1
Order By: Relevance
“…Тритерпеноїдні сапоніни, котрі є основними компонентами Anemone flaccida Fr. Schmidt, показали ефективність при лікуванні ревматоїдного артриту як in vitro, так і in vivo [29].…”
Section: «Art Of Medicine»unclassified
“…Тритерпеноїдні сапоніни, котрі є основними компонентами Anemone flaccida Fr. Schmidt, показали ефективність при лікуванні ревматоїдного артриту як in vitro, так і in vivo [29].…”
Section: «Art Of Medicine»unclassified
“…Schmidt is effective in the prevention of RA by inhibiting bone differentiation and reconstruction (Kong et al, 2015;Liu et al, 2015). Research by Rao et al has indicated that A. flaccida F. Schmidt effectively suppresses synovial proliferation and angiogenesis in arthritic joints and inhibited VEGFR/PI3K/AKT signaling pathway (Rao et al, 2023).…”
Section: Natural Extractsmentioning
confidence: 99%